FAKTOR-FAKTOR YANG MEMPENGARUHI PERNIKAHAN DINI DI DESA YOGYAKARTA KECAMATAN GADINGREJO KABUPATEN PRINGSEWU TAHUN 2016 - Kameliawati, Feri; Juariyah, Juariyah (Bappeda Kabupaten Pringsewu, 2017)
The early-age marriage influenced by various factors.these factors are social factors, economic, cultural and tourist attractions. Another factor is factor of education and employment. The purpose of this study is to determine the factors that influence the early-age marriage in desa Yogyakarta kecamatan Gadingrejo kabupaten Pringsewu. This type of research used in this research is quantitative. The research design was cross-sectional to be used. The research was conducted in March 2017 at desa Yogyakarta kecamatan Gadingrejo kabupaten Pringsewu. Population is 128 couple of perents at marry his daughter, samples were taken by simple random sampling technique of 128 as many as 97 couple of parent. Measuring devices in the form of a checklists sheet in univariate analysis whit the percentage table and bivariate percentage table whit chi square analysis and multivariate percentage table whit regresi logistic analysis. The result of the research shows that most factors related to early marriage in desa Yogyakarta kecamatan gadingrejo kabupaten pringsewu tahun 2017 are education factor with p-value 0,423 and Odds Ratio (OR) 138,498. Conclusion of Village head Yogyakarta can cooperate with health workers in village to do outreach in the community at early-age marriage, and developing businesses in the community to improve the economy and open new create jobs for residents.